Quality and Cost-Effectiveness in Pharmaceutical Procurement: Strategies and a Systematic Review - Alahmar, Mohammed Ali; Fatimah Ali Ahmad Shabi,; Noura Hassan Mohammed Safi,; Amal Saleh Adam Faraj,; HAssan Shabi alagedi,; Masaad Awadh Almutairi,; Huda Omar Salhia,; Ebtisam Ali Aljaizani,; Sulaiman Qaem Alanazi,; Sultan Saad alshehri,; Ahmad Abdullah Alkaabi,; Houson Ali Aloudah,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pharmaceutical procurement is a critical function of the healthcare system in ensuring public health, medicine security, and fiscal sustainability. Inefficient procurement bears the triple risk of essential medicine stockouts, infiltration of substandard drugs, and a tremendous waste of funds, making it a persistent challenge to balance quality-assured access with cost-effectiveness. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes and assesses the evidence from 2015 to 2024 about strategies and frameworks tested to improve the quality assurance and cost-effectiveness of public sector pharmaceutical procurement. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The following databases - PubMed, Scopus, Web of Science, and EMBASE - were systematically searched for peer-reviewed studies, with relevant keywords, between the period of 2015 and 2024. Included empirical studies, reviews, and case studies from various income settings were thematically analyzed via narrative synthesis. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The evidence highlights a toolkit of interlinked strategies. On cost-effectiveness, pooled procurement mechanisms, such as national/regional tenders, attained substantial price reductions (15-40%), whereas stringent generic medicine policies formed the foundation for cost containment. For quality, a tight suppliers' pre-qualification, reliance on WHO/ Stringent Regulatory Authorities, and post-market surveillance were indispensable features. Certain integrated strategies, such as Quality-assured Framework Agreements, came out successful in accommodating both objectives. Main barriers to implementation included political interference, insufficient workforce capacity, and fragmented information systems. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusions:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A holistic, multi-pronged approach is needed, recognizing procurement as strategic in scope, not just an administrative function. Recommendations range from institutionalizing open, data-driven decision-making to investing in workforce capacity, designing quality-weighted tenders, and integrating digital tools. Future studies could focus on the longitudinal impact on health and specific anti-corruption frameworks.